Institutional and informal support for disabled people - Florek, Magdalena (Polish Journal of Public Health, 2009)
Disability is a social phenomenon gradually increasing in size both in Poland and in many other European countries. At the same time, it is one of the most important aspects of the health status. Its causes include a regressive social structure manifested in aging of societies due to a decrease in birth rate with a simultaneous increase in the span of life, followed by a deteriorated physical and mental dexterity. Other sources of disability are traumas sustained in accidents, and diseases. According to the recent General National Census, in 2002 every seventh person living in Poland was disabled, while in 1988 – it was every tenth person, and in 1978 – every fourteenth one. Women and rural inhabitants prevail in the total number of the disabled. The population of disabled people, apart from their health status, experience a number of other limitations and barriers that are significant hindrances for them to function properly in the society. The barriers are usually divided according to their nature into social and physical, and the latter – into physiographic and technical (including architectural, urban, communication and functional).In order to improve the quality of life of people with disabilities, legislative activities are conducted to establish the actors of rehabilitation policy; there are also institutions and organizations, with varying profiles and range of impact. Along with the institutionalised initiatives, there are also informal ones, based on direct interpersonal contacts (e.g. self-help groups, volunteers assistance).Both institutional and informal activities undertaken on behalf of the disabled are oriented towards creating equal opportunities for the disabled and social integration.